Cardiac Imaging in Liver Transplantation Candidates: Current Knowledge and Future Perspectives - Dimitroglou, Yannis (J Clin Med, 2019)
Cardiovascular dysfunction in cirrhotic patients is a recognized clinical entity commonly referred to as cirrhotic cardiomyopathy. Systematic inflammation, autonomic dysfunction, and activation of vasodilatory factors lead to hyperdynamic circulation with high cardiac output and low peripheral vascular resistance. Counter acting mechanisms as well as direct effects on cardiac cells led to systolic or diastolic dysfunction and electromechanical abnormalities, which are usually masked at rest but exposed at stress situations. While cardiovascular complications and mortality are common in patients undergoing liver transplantation, they cannot be adequately predicted by conventional cardiac examination including transthoracic echocardiography. Newer echocardiography indices and other imaging modalities such as cardiac magnetic resonance have shown increased diagnostic accuracy with predictive implications in cardiovascular diseases. The scope of this review was to describe the role of cardiac imaging in the preoperative assessment of liver transplantation candidates with comprehensive analysis of the future perspectives anticipated by the use of newer echocardiography indices and cardiac magnetic resonance applications.